2019
DOI: 10.4085/1062-6050-201-17
|View full text |Cite
|
Sign up to set email alerts
|

The First Decade of Web-Based Sports Injury Surveillance: Descriptive Epidemiology of Injuries in US High School Girls' Lacrosse (2008–2009 Through 2013–2014) and National Collegiate Athletic Association Women's Lacrosse (2004–2005 Through 2013–2014)

Abstract: Context The advent of Web-based sports injury surveillance via programs such as the High School Reporting Information Online (HS RIO) system and the National Collegiate Athletic Association Injury Surveillance Program (NCAA-ISP) has aided the acquisition of girls' and women's lacrosse injury data. Objective To describe the epidemiology of injuries sustained in high school girls' lacrosse in the 2008–2009 through 2013–2014 aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…2 Parallel to the increase in popularity and participation, epidemiologic studies of injuries related to women's lacrosse athletes have emerged and identified the burden of injury in this sport. 1,[3][4][5][6] The sustained rise in women's collegiate lacrosse sponsorship and participation necessitates routine epidemiologic investigation into the nature and incidence of injuries in this population.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…2 Parallel to the increase in popularity and participation, epidemiologic studies of injuries related to women's lacrosse athletes have emerged and identified the burden of injury in this sport. 1,[3][4][5][6] The sustained rise in women's collegiate lacrosse sponsorship and participation necessitates routine epidemiologic investigation into the nature and incidence of injuries in this population.…”
mentioning
confidence: 99%
“…7 Continued monitoring of athletic injury is currently accomplished electronically via the NCAA Injury Surveillance Program (ISP). 7,8 Prior researchers using data from the NCAA ISP have identified the overall injury rate in women's lacrosse as approximately 4 injuries per 1000 athlete exposures (AEs) 3,5 ; however, until recently, nontime loss (NTL) injuries were not included in the analyses. In addition, the Division III injury rate has been noted to be higher than the Division I injury rate, and the rate of injury during competitions has been reported as more than twice as high as the practice injury rate.…”
mentioning
confidence: 99%
See 3 more Smart Citations